High‐sensitivity OAM phase gradient detection based on time‐modulated harmonic characteristic analysis. Issue 12 (1st June 2017) - Chen, Jingfeng; Liang, Xianling; He, Chong; Geng, Junping; Jin, Ronghong
Abstract : A novel phase gradient method for detecting orbital angular momentum modes is proposed. By utilising a two‐element time‐modulated array, the phase gradient of the received signal is estimated through analysing the modulated harmonic component. The bit error rate performances are evaluated using Monte‐Carlo simulation. Results show that the sensitivity strongly depends on the number of sampling modulation pulses. Compared with the conventional phase gradient receiver, the proposed method obviously enhances the performance of detection.